HUBUNGAN KONSUMSI MAKANAN DENGAN KEJADIAN HIPERTENSI PADA LANSIA DI DESA MEKAR BAHALAT KECAMATAN JAWA MARAJA BAH JAMBI KABUPATEN SIMALUNGUN TAHUN 2016 - Ira Lauramoito Gultom; Evawany Y Aritonang; Etti Sudaryati (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2016)
Hypertension is now a risk factor for morbidity and mortality for the elderly. Riskesdas 2013 mentioned that the prevalence of hypertension in Indonesia ranges from 25.8% and the incidence of this disease is more common in women (28.8%) and in the elderly group. In North Sumatra, the prevalence of hypertension is about 24.7% based on Riskesdas 2013. Data from Puskesmas in Mekar Bahalat village 2015 mentioned that the prevalence of hypertension in the elderly is about 21 people (8.8%). The purpose of this study was to determine and analyze the correlation between food consumption with the incidence of hypertension in the elderly in Mekar Bahalat village, District of Jawa Maraja Bah Jambi, Simalungun. This research type is an analytic observational study with cross sectional design. The population in this study were all elderly that aged ≥ 60 years in Mekar Bahalat village that totaling 120 people, and the samples are 55 respondents. This research was in Mekar Bahalat village, District of Jawa Maraja Bah Jambi, Simalungun in September 2015 to May 2016. The results of this research showed that the type of food detterents hypertension that often consumed by the respondents are corn, fresh water fish, tempeh, tomatoes, bananas, green beans and the type of food triggers hypertension that often consumed by the respondent are pork, salted fish, and biscuits. The results also showed that the variables were significantly related to the incidence of hypertension is variable fat (p = 0.025), sodium (p = 0.039) and fiber (p = 0.029), while the variable carbohydrate (p = 0.821) and protein (p = 0.189 ) is not significantly related to the incidence of hypertension. The advice can be given to people in Mekar Bahalat especially the elderly is to reduce the consumption of foods that high in sodium or salt, high fat, and also increase consumption of fruits and vegetables at affordable prices every day. Keywords: hypertension, the elderly, food consumption